Practitioner's guide to using research for evidence-based practice - Rubin, Allen; Bellamy, Jennifer (Hoboken, N.J. : Wiley, 2012)
"Practitioner's Guide to Using Research for Evidence-Based Practice gives essential and practical guidance on how to integrate research appraisal into evidence-based practice endeavors to ensure best client care. This practitioner-oriented book provides readers across the helping professions with the step-by-step skills they need to effectively appraise and use research as part of the evidence-based practice process. Readers will have the ability to integrate evidence-based treatments that improve the delivery of care and optimize treatment success as a result"--
Machine generated contents note: PART I OVERVIEW OF EVIDENCE-BASED PRACTICE Chapter 1 INTRODUCTION TO EVIDENCE-BASED PRACTICE Chapter 2 STEPS IN THE EBP PROCESS Chapter 3 RESEARCH HIERARCHIES: WHICH TYPES OF RESEARCH ARE BEST FOR WHICH QUESTIONS? PART II CRITICALLY APPRAISING STUDIES FOR EBP QUESTIONS ABOUT INTERVENTION EFFECTIVENESS Chapter 4 CRITERIA FOR INFERRING EFFECTIVENESS: HOW DO WE KNOW WHAT WORKS? Chapter 5 CRITICALLY APPRAISING EXPERIMENTS Chapter 6 CRITICALLY APPRAISING QUASI-EXPERIMENTS: NONEQUIVALENT COMPARISON GROUPS DESIGNS Chapter 7 CRITICALLY APPRAISING QUASI-EXPERIMENTS: TIME-SERIES DESIGNS AND SINGLE-CASE DESIGNS Chapter 8 CRITICALLY APPRAISING SYSTEMATIC REVIEWS AND META-ANALYSES PART II CRITICALLY APPRAISING STUDIES FOR ALTERNATIVE EBP QUESTIONS Chapter 9 CRITICALLY APPRAISING NONEXPERIMENTAL QUANTITATIVE STUDIES Chapter 10 CRITICALLY APPRAISING QUALITATIVE STUDIES PART IV ASSESSING CLIENTS AND MONITORING THEIR PROGRESS Chapter 11 CRITICALLY APPRAISING AND SELECTING ASSESSMENT INSTRUMENTS Chapter 12 MONITORING CLIENT PROGRESS APPENDIX A Illustrative Answers to Selected Review Exercises APPENDIX B What You Do and Don't Need to Know about Statistics When Critically Appraising Studies
Includes bibliographical references (p. 345-349) and index.
Keywords: Psychotherapy -- Research -- Methodology; Psychotherapy -- Evaluation -- Methodology; Evidence-based psychiatry; Evidence-Based Practice; Psychotherapy; Evaluation Studies as Topic; Outcome and Process Assessment (Health Care)